Sistem Akuntansi Penggajian Pada PT. Socfindo Seumanyam Kabupaten Nagan Raya - Mila Rahmawati; Said Mahdani (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2022)
The payroll system is a series of data processing business activities with effective management of a company's employees, including payroll/remuneration decisions. The purpose of this study is for the author to know and analyze the Process of Calculation and Payment in the payroll accounting system. The type of survey used is descriptive research using data analysis techniques, or qualitative data analysis. Data sources are divided into primary data and secondary data. Primary data were collected through direct interviews with respondents. Secondary data for this study comes from PT Socfindo documents, salaries, literature, and related sources. The results and discussion at PT.Socfindo Seumanyam show that the author can analyze the payroll system which includes related functions, documents used in the payroll system, accounting records and procedures used by the payroll system, and the internal control payroll system applied at PT.Socfindo seumanyam. The payroll system at PT Socfindo has been effective as seen from the presence of the Harvest Plus software system. However, it has not fully supported the company's internal control efforts. There are deficiencies in the payroll process, namely underpayment of salaries and overpayment of salaries.